Thrombolamban, the 22-kDa platelet substrate of cyclic AMP-dependent protein kinase, is immunologically homologous with the Ras family of GTP-binding proteins. - White, T E (1990)
Platelet inhibition by agents that increase intracellular levels of cAMP is associated with cAMP-dependent phosphorylation of specific intracellular proteins, including a membrane-associated 22-kDa microsomal protein called thrombolamban. In view of recent studies suggesting that platelets also contain 22-kDa GTP-binding proteins that are homologous with ras-encoded p21 proteins, the present work was undertaken to examine the possibility that thrombolamban and the Ras-like proteins were the same. Platelet microsomes were labeled with [gamma-32P]ATP and the labeled proteins were examined by autoradiography of sodium dodecyl sulfate/polyacrylamide gels. On Western blots of both one-dimensional and two-dimensional gels, thrombolamban immunoreacted with M90, a monoclonal antibody that recognizes the GTP-binding domain of Ras p21 proteins, but not with Y13-259, a monoclonal antibody that recognizes another domain and is specific for Ras proteins. Overlay experiments with unlabeled platelet microsomes demonstrated numerous low molecular weight proteins that bound [alpha-32P]GTP, although none could be identified as thrombolamban. Finally, thrombolamban was immunoprecipitated by M90. These studies show that thrombolamban is a low molecular weight protein that is immunologically related to the Ras family of GTP-binding proteins.